PENERAPAN METODE CERAMAH DAN METODE DEMONSTRASI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VI DI SDN BOTO II - Rohmatun Fitriana; Rohmatin Ramadhani; Siti Aisyah; Devy Habibi Muhammad (Al Arsy: Journal of Education, Management and Islamic Thought, 2026)
This study was motivated by the low learning outcomes of sixth-grade students at SDN Boto II, as indicated by the low percentage of learning mastery in the pre-cycle stage. The purpose of this study was to improve students’ learning outcomes through the implementation of the lecture method and demonstration method in the learning process. This study employed a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model, which consists of four stages: planning, action, observation, and reflection. The research subjects were 19 sixth-grade students of SDN Boto II. Data were collected through observation, tests, and documentation. The data were analyzed using descriptive quantitative and qualitative techniques. The results showed that the implementation of the lecture method and demonstration method was able to improve students’ learning outcomes. In the pre-cycle stage, the average score was 69.74 with a learning mastery percentage of 31.58%. In Cycle I, the average score increased to 71.58 with a mastery percentage of 52.63%. Furthermore, in Cycle II, the average score increased to 76.58 with a mastery percentage reaching 89.47%. In addition, the implementation of both methods also improved students’ activeness, attention, and participation during the learning process. Based on these findings, it can be concluded that the lecture method and demonstration method are effective in improving the learning outcomes of sixth-grade students at SDN Boto II.